2016
DOI: 10.17795/ajnpp-39026
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Sociodemographic Variables on the Quality of Life of Menopausal Iranian Women

Abstract: Background: Menopause is a natural physiological event in women's lives that can potentially have negative effects on their quality of life (QoL). Objectives: The aim of the present study was to explore the extent to which sociodemographic characteristics are related to QoL and to compare the QoL of Iranian women with that of women in other countries. Methods: This cross-sectional study was conducted using cluster sampling of 250 postmenopausal women in Hamadan in the west part of Iran in 2014. The participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Furthermore, children's undesirable behavior was identified as an effective variable on QOL in both groups, possibly by affecting mental health (27). Some studies suggest destructive effects of aging on QOL, especially on physical dimension (28)(29)(30). Age was also found a predictor of QOL in the present study rural women.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, children's undesirable behavior was identified as an effective variable on QOL in both groups, possibly by affecting mental health (27). Some studies suggest destructive effects of aging on QOL, especially on physical dimension (28)(29)(30). Age was also found a predictor of QOL in the present study rural women.…”
Section: Discussionsupporting
confidence: 71%
“…Sample size was estimated as 40 for each group for studying QOL in two groups (α = 0.05, β = 0.02) considering scores of QOL in previous studies. 17 18 …”
Section: Methodsmentioning
confidence: 99%
“…The study by Wlliams et al16 in United State of America showed that demographic characteristics and menopausal symptoms experienced by women influenced their QOL in menopausal period. With increased life expectancy and life time, the QOL become an important issue 17. In other words, if the main challenge of 20th century was increasing life expectancy, the main challenge in 21th century is living with higher quality 18.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall objectives of counseling on self-care in the patients are supporting decision making, self-care behavior, problem solving, active cooperation with health care providers, improving clinical outcomes and improve QOL. 23 24 Therefore, this study has been implemented with the aim of determining the effect of group counseling on self-care behaviors among menopausal women with diabetes.…”
Section: Introductionmentioning
confidence: 99%